Association between Androgenetic Alopecia and Psychosocial Disease Burden: A Cross-Sectional Survey among Polish Men - Roksana Adamowicz; Piotr Załęcki; Anna Dukiel; Danuta Nowicka (Dermatology Research and Practice)
A decline in quality of life in men with androgenetic alopecia (AGA) is frequently reported, so we aimed to evaluate the psychosocial burden related to AGA in Polish male patients with AGA. We enrolled 75 adult patients with AGA. The study was conducted in an outpatient dermatology clinic in Poland. Each participant answered 23 dedicated questions about demographic data, history of the disease, and a psychosocial condition. Overall, 38.7% of patients did not notice any impact of AGA on their contact with other people or activity in their free time; 50.7% of patients observed little or no effect on their relationship with their partner; 60% of patients often or sometimes felt embarrassed by their baldness (mainly those aged 18–25 years; p=0.002); 66.7% of patients reported a rather large negative impact on their self-esteem; and 81.3% of patients sometimes experienced stress in everyday life. We conclude that AGA impairs the emotional condition and social functioning of men of all ages, but particularly of younger men. Broader interventions should be planned to allow access to a psychological and psychosocial support, starting treatment at an early stage of the disease, and involving family physicians in the treatment of AGA.